2022
DOI: 10.1192/j.eurpsy.2022.2320
|View full text |Cite
|
Sign up to set email alerts
|

Social isolation and suicide risk: Literature review and perspectives

Abstract: Background: Suicide is a major public health problem and a cause of premature mortality. With a view to prevention, a great deal of research has been devoted to the determinants of suicide, focusing mostly on individual risk factors, particularly depression. In addition to causes intrinsic to the individual, the social environment has also been widely studied, particularly social isolation. This paper examines the social dimension of suicide etiology through a review of the literature on the relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 59 publications
1
19
0
Order By: Relevance
“…This also indicates that variables other than NSSI may play mediating roles in the relation of sexual minority stigma with suicide risk. According to the psychological mediation framework (Hatzenbuehler, 2009), further studies can incorporate these variables, including rumination, emotional dysregulation, and social isolation, that are risk factors for suicide (Motillon-Toudic et al, 2022; Rogers & Joiner, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This also indicates that variables other than NSSI may play mediating roles in the relation of sexual minority stigma with suicide risk. According to the psychological mediation framework (Hatzenbuehler, 2009), further studies can incorporate these variables, including rumination, emotional dysregulation, and social isolation, that are risk factors for suicide (Motillon-Toudic et al, 2022; Rogers & Joiner, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…We also found 'social isolation' and 'violence' as two of the most common positive SBDH predictors. Prior studies showed a higher association between social isolation and suicide risk 12,[42][43][44][45] . Exposure to violence is also a well-known risk factor for suicidality 12,46,47 .…”
Section: Ensemble Learningmentioning
confidence: 92%
“…Spousal relationships have greater in uence than other forms of social ties, and high-quality marriages[76] are associated with positive health outcomes. Social activities enhance communication, improve cognitive functions, offer emotional support, and thus positively impact older people's health [77,78]. Education enhances health by fostering healthy lifestyles, boosting income, and enhancing subjective well-being [79].…”
Section: From Previous Researchmentioning
confidence: 99%